Bilayer functional interlayer coupling defect and Li-ion channel for high-performance Li-S batteries. (20th December 2022) - Cheng, Zhi; Cong, Zhi; Yang, Chao; Wang, Kaiming; Fan, Xin-Yu; Zhao, Bin; Han, Xiaogang
Highlights: Defect design of Se doping synchronously improves the electronic conductivity and polysulfide adsorption–catalysis capability of MoS2 . rGO/MoSSe functional layer serves as an auxiliary cathode and upper current collector accelerates the electron transport and redox kinetics of polysulfide. The carbon nanofiber layer providing channels for the rapid transmission of Li + improves the reversible capacity at high current densities. The designed Li–S batteries exhibit enhanced capacities and cyclic stabilities. Abstract: Lithium-sulfur (Li-S) batteries have been demonstrated as one of the promising candidates for next-generation energy-storage devices. However, low utilization of active materials, detrimental shuttle effect of lithium polysulfides, and sluggish redox kinetics hamper the commercial applications of Li-S batteries. Herein, we design a bilayer functional interlayer composed of reduced graphene oxide/Se-doped MoS2 (rGO/MoSSe) layer and carbon nanofiber (CNF) layer (rGO/MoSSe@CNF) for high-performance Li-S batteries. The defective structure of Se-doped MoS2 significantly improves the polysulfide adsorption–catalytic ability due to the exposure of more active sites and the adjustment of local electronic structure. Accordingly, the rGO/MoSSe functional layer effectively improves the electrochemical reaction kinetics and cyclic stability. In addition, the CNF layer effectively reduces the transport resistance of Li +, and improves the reversible capacity at high current densities. The Li-S coin cell with rGO/MoSSe@CNF interlayer delivers a remarkable reversible specific capacity of 922.4 mAh g −1 after 140 cycles at 0.2 C and a slow capacity decay rate of 0.057% per cycle over 1000 cycles at 1 C. Moreover, the Li-S pouch cell with rGO/MoSSe@CNF interlayer at sulfur loading of 3 mg cm −2 can maintain a reversible specific capacity of 706.2 mAh g −1 after the rate test and 175 cycles at 0.2 C. Graphical abstract: A bilayer functional interlayer composed of reduced graphene oxide/Se-doped MoS2 (rGO/MoSSe) layer and carbon nanofiber (CNF) layer is designed for Li-S batteries . Defect design of Se doping improves the polysulfide (LPSs) adsorption–catalytic ability of MoS2 . The rGO/MoSSe functional layer serves as an auxiliary cathode and upper current collector, improving LPSs redox kinetics and cyclic stability. The CNF layer providing channels for the rapid transmission of Li + improves the reversible capacity at high current densities. Image, graphical abstract